2013
DOI: 10.1371/journal.pone.0077334
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Non-Conventional T Cells and NK Cells in the Mycobacterial-Specific IFNγ Response in Bacille Calmette-Guérin (BCG)-Immunized Infants

Abstract: BackgroundThe Mycobacterium bovis Bacille Calmette-Guérin (BCG) vaccine is given to >120 million infants each year worldwide. Most studies investigating the immune response to BCG have focused on adaptive immunity. However the importance of TCR-gamma/delta (γδ) T cells and NK cells in the mycobacterial-specific immune response is of increasing interest.MethodsParticipants in four age-groups were BCG-immunized. Ten weeks later, in vitro BCG-stimulated blood was analyzed for NK and T cell markers, and intracellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 55 publications
0
51
1
1
Order By: Relevance
“…These enriched CD4 Ϫ CD8 Ϫ TCR-␣␤ ϩ T cells had significantly higher mRNA levels for IFN-␥ and IL-2, highlighting the need to look for correlates of protection in nontraditional CD4 ϩ and CD8 ϩ T cells. In support of this, IFN-␥-expressing DN T cells were observed in BCG-immunized children (78).…”
Section: Cd4 ؊ Cd8 ؊ Dn T Cells a Rare Subset Of T Cells That Are Cd3mentioning
confidence: 58%
“…These enriched CD4 Ϫ CD8 Ϫ TCR-␣␤ ϩ T cells had significantly higher mRNA levels for IFN-␥ and IL-2, highlighting the need to look for correlates of protection in nontraditional CD4 ϩ and CD8 ϩ T cells. In support of this, IFN-␥-expressing DN T cells were observed in BCG-immunized children (78).…”
Section: Cd4 ؊ Cd8 ؊ Dn T Cells a Rare Subset Of T Cells That Are Cd3mentioning
confidence: 58%
“…A previous study reported BCG-induced unconventional CD4 − CD8 − T cells, including γδ T cells and possibly NK cells, in 10-week old infants with no prior mycobacterial sensitization who had received BCG at birth (46). Since BCG-induced conventional CD4 and CD8 T cell response peaks at 10 weeks of age (47), it is possible that BCG-reactive recall response by unconventional cells was indirectly activated by cytokines expressed by BCG-specific conventional T cells.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19] In fact, IFNc production by these cells was greater than that of CD4 + T cells. Similarly to natural infection, cd Tcell populations expand and produce IFNc in response to BCG vaccination.…”
Section: Mycobacteria and Other Bacterial Infectionsmentioning
confidence: 91%